Composition of begomovirus populations in cultivated and non-cultivated hosts determined by high-throughput sequencing - Quadros, Ayane Fernanda Ferreira (2019)
The genus Begomovirus (family Geminiviridae) includes single-stranded DNA plant viruses transmitted by whiteflies. Begomoviruses are among the most damaging plant pathogens, causing epidemics in economically important crops worldwide. Tomato-infecting begomoviruses emerged in Brazil in the early 1990's following the introduction of Bemisia tabaci Middle East-Asia Minor 1 (MEAM1, previously known as B. tabaci biotype B). Several lines of evidence indicate that these viruses evolved from indigenous viruses infecting non- cultivated hosts. However, tomato-infecting viruses are only rarely found in non-cultivated hosts, and vice-versa. It is possible that viral populations in a given host are composed primarily of viruses which are better adapted to this host, but also include a very small proportion of viruses which are poorly adapted. Then, after transfer to a different host by the whitefly vector, the composition of the viral population shifts rapidly, with the viruses which are better adapted to the new host becoming predominant. To test this hypothesis, we collected tomato and Sida sp. plants, growing next to each other, at two locations (Coimbra and Florestal, both in Minas Gerais state, Brazil), in 2014 and 2018. Viral infection was confirmed by by polymerase chain reaction (PCR) using specific primers. Total DNA from one tomato and one Sida sp. sample from each location and year (except Florestal/2018) were sequenced on the Illumina HiSeq 2000 (2014) and NovaSeq 6000 (2018) platforms. Following a highly stringent set of criteria (E-value cutoff of 1.10 -10 ), reads were mapped using BLASTn to a data set including all New World begomoviruses. The reads were classified as (i) Tomato severe rugose virus (ToSRV), (ii) Sida micrantha mosaic virus (SiMMV) and (iii) Sida common mosaic virus (SiCmMV), when the first three hits were isolates of these species, or (iv) begomovirus, when the first three hits included isolates of different species. To resolve the results at the analysis interface and to minimize false positives, mapping was performed using reference sequences from the samples collected. For the 2014 samples, >98% of the reads from Sida sp. mapped to SiMMV, but 0.01% of the reads mapped to ToSRV. Conversely, >99% of the reads from tomato mapped to ToSRV, with 0.001% mapping to SiMMV. For the 2018 samples, the results indicate an increase in the diversity of viruses infecting Sida sp. (including SiMMV, SiCmMV and Abutilon viruses), but 0.1% of the reads mapped to ToSRV. These results are consistent with the hypothesis that viral populations in a given host are composed primarily of the virus that is most adapted to this host but also includes a very small proportion of viruses that are less adapted. Keywords: Begomovirus. Tomato. Sida sp.